American Writers in Europe
VIII, 247 p.
Keywords: These essays explore the impartial critical outlook American writers acquired through their experiences in Europe since 1850. Collectively, contributors reveal how the American writer's intuitive sense of freedom, coupled with their feeling of liberation from European influences, led to intellectual independence in the literary works they produced.